Factors Influencing the Practice of Breast Self-Examination among Female Tertiary Students in Ho, Ghana - Rosemary Ami Amegbedzi; Joyce Komesuor; Hubert Amu; Elvis Enowbeyang Tarkang (Advances in Public Health)
Background. Despite the implementation of various interventions towards the reduction of breast cancer prevalence, many women still report late symptoms to health facilities, and this decreases their chances of survival. Breast self-examination (BSE) is the most convenient form of examination to detect the development of breast cancer. We examined the factors that influence the practice of breast self-examination among female tertiary students in Ho, Volta Region of Ghana. Methods. This was a descriptive cross-sectional study that recruited 506 female students from four tertiary institutions in the Ho Municipality in Ghana using questionnaires. Descriptive and inferential statistics comprising frequency, percentage, Chi-square, and binary logistic regression were used in analyzing the data. Results. About 73% of the respondents had ever practised BSE. Out of the respondents who have ever practiced BSE, 79% were practising it at the time of the study. Students in their fourth year were above 4 times more likely (95% CI = 1.73–9.29, p=0.014) to practise BSE than those in their first year. Also, students with good knowledge of BSE were 4 times more likely to practice BSE [(95% CI = 1.1–13.46), p=0.036] and students with good perception about BSE were 12 times more likely to practice BSE [(95% CI = 1.21–122.73), p=0.034]. Conclusion. The study found that 27% of the female students had never practised BSE. Those who practice BSE did not practice regularly and appropriately. Also, good knowledge and perception are associated with the practice of BSE. The implication of this result is the late presentation of breast cancer cases to health facilities and increases in breast cancer-related deaths in the country. Therefore, it is recommended that the Ministry of Health, the Ghana Health Service, and other stakeholders in Ghana’s healthcare should develop and implement innovative approaches and policies such as peer and support groups’ learning, and mass media BSE awareness aimed at ensuring better understanding and access to BSE education. This should be intensified during the foundation years such as the secondary and tertiary education levels to ensure the adoption of breast self-examination practice. It is also recommended that another study must be done using a qualitative approach to get an in-depth understanding of the steps and ways, by which female students practice BSE.